Emerging Signs of Strong Reciprocity in Human Ontogeny - Robbins, Erin; Rochat, Philippe (Frontiers in Psychology, 2011)
Strong reciprocity is considered here as the propensity to sacrifice resources to be kind or to punish in response to prior acts, a behavior not simply reducible to self-interest and a likely force behind human cooperation and sociality. The aim was to capture emerging signs of strong reciprocity in human ontogeny and across highly contrasted cultures. Three- and 5-year-old middle class American children (N = 162) were tested in a simple, multiple round, three-way sharing game involving the child, a generous puppet, and a stingy puppet. At the end of the game, the child was offered an opportunity to sacrifice some of her personal gains to punish one of the puppets. By 3 years, American children demonstrate a willingness to engage in costly punishment. However, only 5-year-olds show some evidence of strong reciprocity by orienting their punishment systematically toward the stingy puppet. Further analyses and three additional control conditions demonstrate that such propensity is not simply reducible to (a) straight imitation, or (b) inequity aversion. To assess the relative universality of such development, a group of 5- to 6-year-old children from rural Samoa (N = 14) were tested and compared to age and gender-matched American children. Samoan children did not manifest the same propensity toward strong reciprocity. The results are interpreted as pointing to (1) the developmental emergence of an ethical stance between 3 and 5 years of age, and (2) that the expression of such stance by young children could depend on culture.